Pembentukan Karakter Streetscape melalui Bangunan, Pedestrian, dan Public Art di Koridor R.E. Martadinata, Surakarta - Yunanto Nugroho; Titis Srimuda Pitana; Kusumaningdyah Nurul Handayani (Universitas Sebelas Maret Surakarta, 2025)
Character Building of Streetscape through Buildings, Pedestrians and Public Art in the R.E. Martadinata Corridor, SurakartaA visual study of the streetscape character of Jalan R.E. Martadinata examines how this main commercial corridor in the Pasar Gede Surakarta area shapes spatial experience through its visual elements. Using a qualitative case study approach, the analysis focused on buildings, roads, sidewalks, urban elements, and public art. Results show the corridor's visual character is formed by the continuity of two-story shop house facades, where approximately 50–55% of second-floor facades retain their original form, creating strong visual rhythm. Conversely, ground floors have undergone intensive commercial modifications, producing heterogeneous visual variations. Sidewalks function as active visual spaces, particularly after the 2012 revitalization introducing 12 Chinese zodiac motifs and Javanese roof symbols. Public art—including lanterns, coin ornaments, and festival decorations—serves as marker elements reinforcing area identity. Overall, the streetscape's visual character results from interactions between tradition, modernization, and cultural expression.